Implementing PERFECT-ER with Plan-Do-Study-Act on acute orthopaedic hospital wards: Building knowledge from an implementation study using Normalization Process Theory. - Chris Fox; Simon P Hammond; Tamara Backhouse; Fiona Poland; Justin Waring; Bridget Penhale; Jane L Cross (PLoS ONE, 2023)
Background Delivering care to growing numbers of patients with increasingly 'complex' needs is currently compromised by a system designed to treat patients within organizational clinical specialties, making this difficult to reconfigure to fit care to needs. Problematic experiences of people with cognitive impairment(s) admitted to hospitals with a hip fracture, exemplify the complex challenges that result if their care is not tailored. This study explored whether a flexible, multicomponent intervention, adapting services to the needs of this patient group, could be implemented in acute hospital settings. Methods We used action research with case study design to introduce the intervention using a Plan-Do-Study-Act (PDSA) model to three different hospital sites (cases) across England. The qualitative data for this paper was researcher-generated (notes from observations and teleconference meetings) and change agent-generated (action plans and weekly reflective reports of change agents' activities). Normalization Process Theory (NPT) was used to analyze and explain the work of interacting actors in implementing and then normalizing (embedding) the intervention across contexts and times. Data analysis was abductive, generating inductive codes then identified with NPT constructs. Across the three cases, change agents had to work through numerous implementation challenges: needing to make sense of the intervention package, the PDSA model as implementation method, and their own role as change agents and to orientate these within their action context (coherence). They had to work to encourage colleagues to invest in these changes (cognitive participation) and find ways to implement the intervention by mobilising changes (collective action). Finally, they created strategies for clinical routines to continue to self-review, reconfiguring actions and future plans to enable the intervention to be sustained (reflexive monitoring). Conclusions Successful implementation of the (PERFECT-ER) intervention requires change agents to recognize and engage with local values, and then to enable its fit with practice and wider contextual goals. A context of constant change fragments normalization. Thus, sustaining practice change over time is fragile and requires change agents to continue a recursive two-way sense-making process. This enables implementation and normalization to re-energize and overcome barriers to change.